Malaria “chemoprevention and vaccination strategies” for children living in endemic areas of Africa: a review - Nambatya, Winnie; Ocan, Moses; Robberstad, Bjarne; Achan, Jane; Idro, Richard (Frontiers in Malaria, 2025)
There has been significant progress in malaria prevention over the past 20 years, but the impact of current interventions may have peaked and in moderate to high malaria transmission areas, the earlier gains either have since stalled or reversed. Newer and more innovative strategies are urgently needed. These may include different chemoprevention strategies, vaccines, and injectable forms of long-acting antimalarial drugs used in combination with other interventions. In this paper, we describe the different chemoprevention strategies; their efficacy, cost-effectiveness, uptake, potential impact, and contextual factors that may impact implementation. We also assess their effectiveness in reducing the malaria burden and emerging concerns with uptake, drug resistance, stock-outs, funding, and equity and suggestions to improve application.